2016
DOI: 10.1149/2.0131609jes
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Seeding and Electroless Cu Plating on TaN Barrier Layers: The Role of Plasma Functionalized Self-Assembled Monolayers

Abstract: Self-assembled monolayers (SAMs) are extensively used in microelectronic copper metallization primarily as seed-trapping layers, diffusion barriers, or pore-sealants for porous dielectric materials. However, direct electroless copper plating of nitride barrier layers assisted by a seed-trapping SAM is rarely examined. Therefore, this work uses TaN, a standard barrier material for Cu metallization, as a model substrate to develop a new seeding (catalyst formation) process for electroless copper plating, involvi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 44 publications
0
2
0
Order By: Relevance
“…The used highly porous low-k materials in this study are SiOCH films with a k value of 2.25, deposited on 300 mm p-type silicon wafers using plasma-enhanced chemical vapor deposition (PECVD, Applied Materials, Santa Clara, CA, USA) method [19]. The average pore size and porosity of the resulting highly porous low-k films are around 1.15 nm and 32.0%, respectively, which were determined from the isotherm of ethanol adsorption and desorption using ellipsometric porosimetry.…”
Section: Methodsmentioning
confidence: 99%
“…The used highly porous low-k materials in this study are SiOCH films with a k value of 2.25, deposited on 300 mm p-type silicon wafers using plasma-enhanced chemical vapor deposition (PECVD, Applied Materials, Santa Clara, CA, USA) method [19]. The average pore size and porosity of the resulting highly porous low-k films are around 1.15 nm and 32.0%, respectively, which were determined from the isotherm of ethanol adsorption and desorption using ellipsometric porosimetry.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, the seed densities for the two Ta films can be traced back from the distribution densities of the copper islands before they coalesce into a continuous film. 43 Analyzing such SEM images, as demonstrated in Fig. S4 (Cu plated for only 3 s), using an open source image processing program (ImageJ) revealed that the seeds densities of the anhydrously and hydrously anodized Ta films were 7.9 × 10 14 m −2 and 5.2 × 10 15 m −2 , respectively.…”
mentioning
confidence: 99%